Study of Urban Milk Supply Schemes - Planning Commission (Planning Commission, 1970)
The papers on methodology, objectives, scope, sampling design, guide points, schedules and questionnaires and instructions thereon have been got together in the form of a compendium for the convenience of the officers engaged on the study. The papers have been finalised on the basis of the seminar held for the purpose which was attended by the Regional Evaluation Officers in addition to the Senior Officers of the PEO at the Headquarters and the representative of the concerned Divisions of the Planning Commission. The comments received from some of the expert in the line in the country have also been suitably incorporated. It is hoped that the field officers will find the compendium complete, self-explanatory and handy.
Design, Schedules, Etc., and Instructions